Laughter Before Sleep. - Pack, Robert (University of Chicago Press, 2011)
One of America's most eminent nature poets, Robert Pack has won the acclaim of writers, critics, and readers from Stephen Jay Gould to Mark Strand. In his latest collection, Laughter Before Sleep, Pack carries on his themes of family and friends, responsibility to the natural world of evolved diversity, the transience of life, the fragility of happiness, and the consolations offered by art and music. Laughter Before Sleep weighs the nature of endings from the perspective of old age and embraces the humor and play of memory that keep mortality at bay. As we are carried along with Pack'.